Analisis Perputaran Modal Kerja Pada PT. Lippo Karawaci, Tbk - Nulkarim, Riziku; Muniarty, Puji (Ekopem: Jurnal Ekonomi Pembangunan, 2023)
This study aims to determine and analyze the amount of working capital turnover at PT. Lippo Karawaci, Tbk. This type of research is descriptive using secondary data sources. The research instrument used is a list of tables containing sales data, current assets, current liabilities, at PT. Lippo Karawaci, Tbk for 10 years, from 2012 to 2021. The population used in this research is all of the financial statements of PT. Lippo Karawaci, Tbk since being listed on the IDX from 1996 to 2021, namely for 25 years. The sample is 10 years from 2012 to 2021 using a purposive sampling technique. Data collection techniques using documentation and literature study. The data analysis technique uses a one-sample t-test. The results showed that the working capital turnover at PT. Lippo Karawaci, Tbk more than 6 times than expected or good.